Ethnic differences in use values and use patterns of Parkia biglobosa in Northern Benin - Koura Kourouma; Ganglo Jean C; Assogbadjo Achille E; Agbangla Clément (BMC, 2011)
Abstract Background African locust bean tree (Parkia biglobosa) is a multipurpose species used widely in arid Africa by local communities. The present study focused on ethnic differences in use values and use patterns of P. biglobosa in Northern Benin, where the species widely grows. The use values according to the various ethnic groups in the study area have been evaluated in detail for P. biglobosa. Methods From 13 ethnic groups, 1587 people were interviewed in the study area using semi-structured questionnaires. Principal Component Analysis was applied to analyze the use value and the use patterns of P. biglobosa for the different ethnic groups. Results All interviewees in the study area knew at least one use of P. biglobosa. The various uses identified were medicinal (47%), handicraft and domestic (3%), medico-magic (1%), veterinary (1%), cultural (1%), food (25%) and commercial (22%). The various parts involved in these types of uses were: fruits [shell (2%), pulp (22%) and seeds (36%)], bark (17%), leaves (9%), roots (3%), flowers (1%) and branches (10%). The ethnic group consensus values for P. biglobosa parts showed that the seeds are used the most. The interviewees diversity value (ID) and equitability value (IE) indicated that knowledge concerning P. biglobosa use was distributed homogeneously among the ethnic groups. Conclusions P. biglobosa is well-known and used in different ways by the local populations in the study area. Local knowledge on the species is diversified and influenced by ethnic group. Ethnic differences in use values and use patterns of the species were evident in this study.